DEVELOPMENT OF PROFESSIONAL TRAINING OF FUTURE MILITARY EDUCATION TEACHERS TECHNOLOGICAL PEDAGOGI - CAL CONDITIONS. (Scientific journal of the Fergana State University, 2023)
In this article, the preparation, personal qualities, and essence of the future teachers of military education, the development of their level of knowledge and professional training, as well as the regular education and training of students and young people, always raising the spirit of military patriotism, as well as worthy of the borders of our independent Motherland it is shown that they are always ready to protect, and it states that the main goal of military education teachers is to successfully provide knowledge and education to students and youth, and to regularly develop their professional training.In the article, the process of education and upbringing of students is an activity aimed at the professional training of future teachers of military education, in the framework of which not only their military skills are formed and developed, but also students embody morally mature and moral qualities, it is emphasized that mentally and physically healthy, socially active and well-rounded human personality should be brought up. As we mentioned above, general approaches to the unified interpretation of the concept of educational technology in modern pedagogy in the provision of knowledge and education to young students have not yet been developed, there is no unified classification, but in higher educational institutions there are wide classifications of educational technologies according to didactic theories. It has been mentioned that it is being used. The article also presents scientific-philosophical analyzes of the traditional approach, systematic modern approach, technological approach, critical approach, and complex activity approaches in the technologies of teaching young students and educational practices.